Seven Demotic Votive Inscriptions on Various Objects from the Tuna al-Gebel Necropolis - Ebeid, Mahmoud (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
Publication of seven Demotic votive inscriptions written on various materials, from the Tuna al-Gebel necropolis, now kept in the Tuna al-Gebel magazine, the Mallawi Museum, and al-Ashmunein magazine.